Tetrahedral mesh generator for CFD simulation of complex geometry - Luon N.Y.; Yusoff M.Z.; Shuaib N.H. (2023)
Computational Fluid Dynamics (CFD) simulation is becoming an important aspect in the design and analysis of engineering equipment. CFD allows engineers to reduce losses related to fluid flows and hence increase the performance. The first part of CFD simulation is building suitable mesh for the geometry to be analyzed. Tetrahedral mesh is widely used in meshing complex domain due to its flexibility. One of the common techniques used to generate tetrahedral mesh is Delaunay triangulation. Although Delaunay triangulation can always generate tetrahedral elements that fill any domain, the quality of the elements is not guaranteed. This is particularly important in CFD simulations whereby the accuracy of results and convergence rate will be highly affected by the mesh quality. This paper describes the development of a tetrahedral mesh generator which is capable of generating sufficiently high quality tetrahedral cells in arbitrary complex geometry. A few test cases are presented which show that slivers are eliminated and the overall quality is good. The combination of the constrained and conforming boundary recovery was also successfully done where all the missing faces are rebuilt. 2009 IEEE.